Improvement of a Traditional Orphan Food Crop, Portulaca oleracea L. (Purslane) Using Genomics for Sustainable Food Security and Climate-Resilient Agriculture - Kumar, Ajay; Sreedharan, Sajana; Singh, Pardeep; Achigan-Dako, Enoch G.; Ramchiary, Nirala (Frontiers in Sustainable Food Systems, 2021)
Purslane (Portulaca oleracea L.) is a popular orphan crop used for its nutritional properties in various parts of the world. It is considered one of the richest terrestrial sources of omega-3 and omega-6-fatty acids (ω-3 and 6-FAs) suggesting its importance for human health. This ethnomedicinal plant is also an important part of traditional healing systems among the indigenous people. Many studies have indicated its tolerance against multiple stresses and found that it easily grows in a range of environmental gradients. It has also been considered as one of the important biosaline crops for the future. Despite its huge nutritional, economic, and medicinal importance, it remains neglected till date. Most of the studies on purslane were focused on its ethnomedicinal, phytochemical, pharmacological and stress tolerance properties. Only a few studies have attempted genetic dissection of the traits governing these traits. Purslane being an important traditional food crop across the globe can be valorized for a sustainable food security in the future. Therefore, this review is an attempt to highlight the distribution, domestication and cultivation of purslane and its importance as an important stress tolerant food and a biosaline crop. Furthermore, identification of genes and their functions governing important traits and its potential for improvement using genomics tools for smart and biosaline agriculture has been discussed.